High temperature proton exchange membrane fuel cell metal bipolar plate coating and method of making
Patent Information
- Application Number
- CN202611294745.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-27
AI Technical Summary
(一)本发明采用Ti过渡层+碳功能层双层复合涂层结构,通过对各工序工艺参数协同控制,涂层可在120℃、pH=3且含氟离子的严苛酸性环境下,保持较低的腐蚀电流密度,有效抑制金属双极板基材腐蚀,解决现有常规涂层仅适配80℃常温燃料电池,高温环境下腐蚀加剧、易失效脱落的技术痛点。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fuel cell electrode coating technology, specifically relating to high-temperature proton exchange membrane fuel cell metal bipolar plate coatings and their preparation methods. Background Technology
[0002] High-temperature proton exchange membrane fuel cells (PEMFCs) can operate at temperatures up to 120°C. Compared to traditional 80°C ambient temperature PEMFCs, they offer significant advantages such as higher carbon monoxide tolerance, simplified hydrothermal management systems, and higher power generation efficiency. Metal bipolar plates are the core conductive and current-collecting components of their stacks. Currently, most metal bipolar plates in the industry use stainless steel or titanium alloy substrates. In a high-temperature acidic environment (120°C, pH≈3, containing fluoride ions), the bare substrate is highly susceptible to electrochemical corrosion. Corrosion products contaminate the proton exchange membrane, and a high-resistance oxide passivation film easily forms on the plate surface, significantly increasing interfacial contact resistance. This leads to a decrease in stack output power and a shortened lifespan. Therefore, a protective conductive coating must be prepared on the surface of the metal bipolar plate to adapt to high-temperature acidic conditions. Most existing commercial coating solutions are only suitable for 80°C ambient temperature fuel cell operation and lack mature coating systems that can stably withstand the 120°C high-temperature acidic corrosion environment over a long period, making it difficult to support the industrialization of high-temperature PEMFCs.
[0003] Currently, metal bipolar plate coatings mainly fall into two technical routes: precious metal coatings and carbon-based coatings. The precious metal route often uses platinum and other precious metal plating, which, while possessing excellent conductivity, results in high raw material costs, significantly increasing the overall manufacturing cost of the fuel cell stack. Furthermore, precious metals catalyze the electrolyte electrolysis reaction in high-potential acidic environments, leading to a significant increase in the coating's self-corrosion current density and a high failure probability during high-temperature durability testing, failing to meet the requirements for long-term high-temperature operation. Conventional single-layer carbon coatings, while exhibiting excellent conductivity, suffer from poor physical adhesion between the carbon film and the metal substrate, making them prone to peeling and flaking during electrochemical cycling. Single-layer titanium protective layers offer acceptable corrosion resistance, but titanium oxidation forms a high-resistance oxide layer, drastically increasing the plate contact resistance. Neither can simultaneously achieve both corrosion resistance and low conductive contact resistance. Existing composite coatings lack a precisely matched layered structure and a suitable PVD (physical vapor deposition) preparation process for high-temperature operating conditions, making it difficult to synergistically optimize film-substrate adhesion, high-temperature corrosion resistance, and conductivity.
[0004] Existing magnetron sputtering processes for coating fabrication lack precise parameters tailored to the harsh operating conditions of high-temperature fuel cells: Eliminating the titanium transition layer directly leads to delamination of the carbon layer from the substrate; excessively long deposition times and thicknesses of the titanium transition layer result in coating failure after high-temperature constant-potential corrosion; excessively high bias voltage during titanium layer deposition deteriorates overall corrosion resistance; and deviations from the optimal pressure range in the carbon functional layer deposition chamber damage the carbon film. 2 / sp 3The structural composition simultaneously degrades conductivity and corrosion resistance; insufficient plasma activation time fails to fully activate the substrate surface, while excessively prolonged activation time does not improve performance but instead increases production energy consumption and processing cycle time. Existing technologies lack systematic examples and comparative studies to clarify the influence of various process parameters and layered structure on corrosion current density, interfacial contact resistance, and coating adhesion under 120℃ high-temperature acidic conditions. A complete preparation scheme for Ti / C bilayer composite coatings that balances industrial-scale mass production, low cost, and long-term high-temperature stability is lacking. Summary of the Invention
[0005] To address the aforementioned technical problems, the first aspect of this invention provides a method for preparing a metal bipolar plate coating for a high-temperature proton exchange membrane fuel cell, comprising the following steps: S1. Pre-treatment before coating: After inspecting the incoming metal bipolar plates, ultrasonically cleaning and drying them, they are transferred to the composite magnetron sputtering coating equipment to clean the target and cavity of the equipment and complete the workpiece mounting. S2, Vacuum Degassing and Plasma Activation: After the cavity is roughly pumped by a mechanical pump, a molecular pump is switched to evacuate the vacuum and degass the cavity by maintaining the temperature; then high-purity argon gas is introduced and the ion source is turned on to perform low-temperature Ar plasma activation treatment. S3. Titanium transition layer deposition: Adjust the argon flow rate to the titanium deposition working pressure, use two high-purity titanium planar magnetron targets to perform titanium transition layer deposition, and obtain a dense titanium transition layer with a thickness of 25~40nm. S4. Carbon functional layer deposition: Adjust the argon flow rate to the carbon deposition working pressure, turn on the graphite multi-arc target, and perform carbon functional layer deposition to obtain a carbon functional layer. S5. Post-processing: After coating is completed, the coating is cooled in a controlled manner, then inspected, packaged, and stored.
[0006] The pretreatment step S1 of this invention removes oil, impurities, and oxide layers from the electrode surface, cleans the chamber and target to eliminate coating contamination sources, and ensures uniform coating of the workpiece by proper mounting. This eliminates defects such as pinholes, peeling, and impurities in the coating, improves the adhesion between the titanium transition layer and the substrate, and ensures consistent coating performance across the entire batch of electrodes. The vacuum degassing and plasma activation treatment in step S2 removes adsorbed water vapor and volatile organic compounds from inside the electrode through high-temperature degassing, and uses low-energy argon ion bombardment to etch the substrate surface and activate the interface. This avoids gas release during the coating process that could cause a loose coating and increases the number of active sites on the substrate surface. The process involves several steps: Step S3 involves depositing a thin, dense titanium intermediate bonding layer between the metal substrate and the outer carbon film to strengthen the adhesion of the titanium transition layer and significantly reduce the risk of coating peeling off under high-temperature and acidic conditions. Step S4 involves depositing a graphite carbon film on the surface of the titanium transition layer to construct a conductive and corrosion-resistant outer functional layer and regulate the spp ratio of the carbon film. This process effectively addresses the issue of easy peeling off of single-layer carbon coatings. The thickness is controlled at 25-40 nm, ensuring bonding strength while preventing excessively thick titanium layers from oxidizing and forming a high-resistance film, thus balancing corrosion resistance and low contact resistance. Step S4 involves depositing a carbon functional layer on the surface of the titanium transition layer to construct a conductive and corrosion-resistant outer functional layer and to regulate the spp ratio of the carbon film. 2 / sp 3 The structural proportions significantly reduce the contact resistance at the electrode interface. The dense carbon layer isolates the acidic corrosive medium and inhibits the electrochemical corrosion of the substrate, greatly reducing production costs compared to Pt precious metal coatings. At the same time, it does not catalyze electrolyte electrolysis. The S5 post-processing controlled cooling and inspection and warehousing slowly cools down to eliminate internal thermal stress in the coating. The non-conforming products are screened by sampling for corrosion and contact resistance, which can avoid cracking and peeling of the coating due to sudden cooling. This ensures that the finished product meets the indicators of low corrosion current and low contact resistance under high temperature acidic conditions of 120℃, and is suitable for the stacking and use requirements.
[0007] As an feasible example, the vacuum degree in step S2 is ≤8×10⁻⁶. -4 Pa. Low residual gas ensures Ar plasma purity, uniform and thorough ion beam etching, and complete removal of microscopic oxide films and contaminants from the substrate surface. This enhances the adhesion between the Ti transition layer and the metal substrate, preventing coating peeling during long-term electrochemical service.
[0008] As a feasible example, the aforementioned heat preservation and degassing treatment is carried out at a temperature of 90~100℃ for 40~50 minutes. The metal bipolar plate substrate, tooling fixtures, and inner walls of the cavity will adsorb volatile impurities such as water vapor and oil decomposition products. Heating at a medium-low temperature of 90~100℃ drives the desorption of adsorbed gases; the 40~50 minute heat preservation time ensures sufficient desorption and prevents residual water vapor and oxygen from oxidizing the titanium film during subsequent plasma activation and titanium layer sputtering stages, forming a high-resistance oxide layer that deteriorates conductivity and corrosion resistance. If the temperature is too low or the time is insufficient, degassing will be incomplete, and residual impurities will continue to contaminate the film.
[0009] As an feasible example, the high-purity argon gas has a purity ≥99.999% and a dew point ≤-60℃. Trace amounts of oxygen, nitrogen, and other impurities in the argon gas will react with active Ti atoms during plasma activation and titanium magnetron sputtering, generating insulating TiO2 and TiN. The titanium oxide interlayer significantly increases the interfacial contact resistance and disrupts the continuity of the Ti transition layer, forming corrosion channels and reducing corrosion resistance in high-temperature acidic environments. 5N-grade high-purity argon can control oxidizing impurities to extremely low levels, ensuring that the Ti layer is a pure metallic, dense thin film.
[0010] As a feasible example, the low-temperature Ar plasma activation treatment uses an Ar flow rate of 57~63 sccm, a working pressure of 0.75~0.85 Pa, an ion source current of 4.7~5.3 A, a treatment time of ≥6 min, and a pulse bias voltage of -240~-260 V. The matching of all parameters in the low-temperature Ar plasma activation treatment results in a moderately strong, uniform, and controllable argon ion etching effect, thoroughly removing the native oxide layer and adsorbed impurities from the surface of the metal bipolar plate, constructing a clean and active substrate interface, and significantly improving the bonding strength between the Ti transition layer and the substrate. Simultaneously, it avoids excessive etching damage to the substrate, ensuring the subsequent Ti / C double-layer coating is dense and complete. Ultimately, the finished product exhibits low contact resistance and low corrosion current density in a 120℃ high-temperature acidic fluorine-containing environment, with a wide process window and stable performance in batch products.
[0011] As an feasible example, the Ar flow rate in step S3 is 20-30 sccm. If the Ar flow rate is below 20 sccm, the number of argon ions in the chamber is insufficient, the plasma density is low, and the sputtering rate decreases. Within a fixed deposition time, the titanium film thickness cannot reach 25 nm, and the transition layer is too thin, resulting in local discontinuities. The carbon functional layer can easily penetrate defects and contact the substrate, causing a decrease in the coating's corrosion resistance. If the Ar flow rate is above 30 sccm, the chamber pressure is too high, and the collision and scattering of titanium sputtered atoms during flight intensifies, reducing the number of particles that effectively reach the substrate. At the same time, the ion backsputtering effect becomes stronger, not only causing fluctuations in the deposition rate but also resulting in a film thickness exceeding 40 nm. The Ti transition layer is too thick, and high-resistance titanium oxide is easily generated in a high-temperature acidic environment. After constant potential corrosion, the coating peels off, and the contact resistance and corrosion current deteriorate simultaneously.
[0012] As an feasible example, the titanium deposition working pressure is 0.1~0.15 Pa, and the preferred titanium deposition working pressure in this invention is 0.12 Pa. If the pressure is too low, there are fewer argon molecules, the mean free path of the titanium sputtering particles is too large, the kinetic energy of the particles bombarding the substrate is too high, the internal stress of the film increases, and microcracks are easily generated. If the pressure is too high, the particles collide with argon gas frequently, resulting in severe kinetic energy loss, easily forming a loose and porous columnar crystalline film, allowing corrosive media to easily penetrate along the pores and reducing corrosion resistance. At 0.12 Pa, titanium atoms possess suitable incident energy, easily forming a fine-grained, low-porosity continuous titanium film.
[0013] As an feasible example, the high-purity titanium planar magnetron target has a single-target power of 4~5kW, a target-substrate distance of 120~150mm, and a purity of ≥99.95%. The single-target power determines the sputtering rate of the titanium target. Lower power results in a lower sputtering rate, making it difficult to form a continuous and complete titanium transition layer within a given deposition time. This easily leads to localized discontinuous defects in the film layer, allowing corrosive media to penetrate the defects and directly erode the substrate, resulting in decreased corrosion resistance. Power higher than 5kW results in an excessively fast sputtering rate, making it easy for the titanium layer thickness to exceed 40nm in the same time. This leads to a thicker titanium transition layer, which is prone to generating high-resistance titanium oxide in a high-temperature acidic environment of 120℃, causing increased contact resistance and even coating peeling.
[0014] As an feasible example, the working bias voltage for the titanium transition layer deposition process is -50 to -100V, and the deposition time is 4 to 5 minutes. The workpiece bias voltage is used to control the titanium ion bombardment energy reaching the substrate. If the absolute value of the bias voltage is too small, the ion bombardment energy is insufficient, the atomic migration ability of the film layer is weak, and a loose and porous Ti film is easily formed with many pore defects. Corrosive media can easily penetrate through the transition layer, causing an increase in corrosion current. If the absolute value of the bias voltage is too large, the ion bombardment energy is too high, and the strong back sputtering effect will re-sputter and peel off the already deposited titanium atoms, reducing the net deposition rate. The film layer is prone to generating large residual internal stress, inducing microcracks, reducing the film-substrate adhesion, and the coating is prone to cracking and peeling off under high temperature and acid conditions in the later stage.
[0015] As a feasible example, the carbon deposition working pressure is 0.07~0.09 Pa. The working pressure directly affects the flight energy of carbon atoms during graphite multi-arc deposition. When the pressure is in the range of 0.07~0.09 Pa, carbon atoms possess suitable mean free path and incident kinetic energy, allowing for reasonable control of sp... 2 Conductive phase sp 3 The high proportion of corrosion-resistant phases gives the carbon functional layer both low contact resistance and excellent resistance to acid corrosion. However, if the pressure exceeds 0.09 Pa, frequent gas collisions occur within the chamber, leading to a significant loss of kinetic energy in carbon atoms. 3 The imbalance in the proportion of carbon film decreases, and the porous nature of the carbon film allows corrosive media to easily penetrate into the film layer, resulting in a significant increase in both corrosion current density and contact resistance.
[0016] As an feasible example, the arc source current in the carbon functional layer deposition process is 50~60A, the peak bias voltage of the workpiece is -37~-43V, and the deposition time is 10~15min. The arc source current determines the ionization degree of the graphite multi-arc target and the carbon particle output flux, directly controlling the carbon film deposition rate. When the current is below 50A, the arc source discharge energy is insufficient, the carbon plasma density is low, the deposition rate is slow, and the carbon film thickness is insufficient in the same time, failing to completely cover the Ti transition layer. Corrosive media can easily penetrate the film layer, causing an increase in corrosion current. When the current is above 60A, the carbon particle flux is too large, the deposition rate is too fast, the film layer is prone to generating large internal stress and microcracks. At the same time, the high current will generate more large graphite droplets, resulting in more surface defects in the film layer and reducing corrosion resistance. The peak bias voltage of the workpiece controls the bombardment energy of carbon ions reaching the workpiece surface, affecting the carbon film sp 2 / sp 3 The structural proportions, density, and internal stress of the film are all factors that contribute to the problem. Insufficient absolute bias voltage leads to inadequate ion bombardment energy, weak carbon atom surface migration, and a tendency for the carbon film to become porous. 3 Insufficient proportion of corrosion-resistant phase leads to decreased corrosion resistance; excessive absolute value of bias voltage results in excessively strong ion bombardment; strong back sputtering effect can erode the already deposited carbon film, while the residual internal stress of the film increases sharply, making the carbon film prone to cracking and disrupting the Ti / C interface bonding. Under acidic conditions at 120℃, there is a risk of coating delamination. -37~-43V can provide moderate ion bombardment, optimize the microstructure of the carbon film, and balance the conductivity sp. 2 Phase and corrosion resistance sp 3 The deposition time is limited to 10-15 minutes. Under the above-mentioned arc source current, bias voltage, and working pressure conditions, the deposition time determines the final film thickness of the carbon functional layer. If the time is less than 10 minutes, the carbon film thickness is insufficient, there are local thin areas in the film layer, the protective integrity is insufficient, and acidic media can easily penetrate and corrode the lower layer. If the time is longer than 15 minutes, the carbon film is too thick, which will increase the interfacial contact resistance. At the same time, the accumulated internal stress of the film layer is too large, which will increase the risk of peeling and detachment, and will also reduce the production cycle, which is not conducive to mass production. A carbon functional layer with suitable thickness and complete continuity can be obtained in 10-15 minutes, which can effectively isolate high-temperature acidic corrosive media and maintain low contact resistance, meeting the requirements of metal bipolar plates for high-temperature proton exchange membrane fuel cells.
[0017] A second aspect of the present invention provides a high-temperature proton exchange membrane fuel cell metal bipolar plate coating obtained by the above preparation method.
[0018] Beneficial effects (i) The present invention adopts a Ti transition layer + carbon functional layer dual-layer composite coating structure. By coordinating the control of process parameters of each process, the coating can maintain a low corrosion current density in a harsh acidic environment containing fluoride ions at 120℃ and pH=3, effectively inhibiting the corrosion of metal bipolar plate substrates. This solves the technical pain point that existing conventional coatings are only suitable for fuel cells at room temperature of 80℃, and corrosion is aggravated and easy to fail and fall off in high temperature environments.
[0019] (ii) By adjusting the process parameters for carbon functional layer deposition, the sp of the carbon film can be precisely controlled. 2 / sp 3 In proportion, sp 2 This ensures good conductivity and achieves low contact resistance under a clamping force of 0.6MPa; 3 This improves the corrosion resistance of the film layer, overcomes the defects of high contact resistance of a single titanium layer and poor bonding force of a simple carbon layer, and achieves synergistic optimization of both conductivity and corrosion resistance.
[0020] (III) The present invention sets a thin and dense Ti transition layer as an intermediate bonding layer, and at the same time combines vacuum degassing and Ar plasma activation pretreatment processes to improve the substrate interface state and solve the problem of easy peeling and detachment when the carbon layer is directly deposited; and strictly limits the thickness range of the Ti transition layer to avoid the problems of high oxidation resistance and coating detachment caused by excessively thick transition layer, thereby improving the long-term service reliability of the coating.
[0021] (iv) This invention uses titanium targets and graphite targets as coating materials, abandoning the platinum and other precious metal coating schemes, which greatly reduces material costs; at the same time, it avoids the defects of precious metals in high potential acidic environment catalyzing electrolyte electrolysis and poor corrosion stability, and is more suitable for industrial promotion while ensuring performance.
[0022] (v) The entire preparation process is based on mature composite PVD equipment. Each key process parameter is set with a reasonable and controllable parameter window. The planetary carrier ensures the uniformity of the coating on the workpiece. The production cycle is controllable and the batch performance is highly consistent. It can prepare metal bipolar plates for high-temperature proton exchange membrane fuel cells on a large scale, which will help the application of high-temperature fuel cells in vehicle and distributed power generation scenarios. Detailed Implementation
[0023] Example 1 The first aspect of this example provides a method for preparing a metal bipolar plate coating for a high-temperature proton exchange membrane fuel cell, specifically comprising the following steps: S1. Pretreatment before coating: The incoming metal bipolar plates are inspected and cleaned with a weak alkaline low-residue cleaning agent (commercially available products, no special restrictions), 18MΩ deionized water, and electronic grade isopropanol in a multi-stage ultrasonic cleaning process. They are then transferred to the composite magnetron sputtering coating equipment to clean the target and cavity of the equipment and complete the workpiece mounting. S2. Vacuum degassing and plasma activation: After rough evacuation of the chamber using a mechanical pump, switch to a molecular pump to evacuate to a base vacuum ≤8×10⁻⁶. -4 Pa, degas at 95℃ for 45 min; then introduce high-purity argon gas (purity ≥99.999%, dew point ≤-60℃), maintain working pressure 0.8 Pa, turn on ion source, ion source current 5.0 A, pulse bias voltage -250 V, and perform low-temperature Ar plasma activation treatment for 6 min. S3. Titanium transition layer deposition: Adjust the argon flow rate (25 sccm) to the titanium deposition working pressure of 0.12 Pa, use two high-purity titanium planar magnetron targets (single target power 5.0 kW, target-substrate distance 150 mm, purity of high-purity titanium planar magnetron targets ≥99.95%), workpiece bias voltage -50 V, and perform titanium transition layer deposition for 4 min at a planetary carrier spindle speed of 5 rpm to obtain a dense titanium transition layer with a thickness of 25~40 nm; S4. Carbon functional layer deposition: Adjust the argon flow rate (5 sccm) to the carbon deposition working pressure of 0.08 Pa, turn on the graphite multi-arc target, set the arc source current to 50 A, and the workpiece peak bias voltage to -40 V to perform carbon functional layer deposition for 12 min to obtain the carbon functional layer. S5. Post-processing: After coating is completed, the coating is cooled in a controlled manner, then inspected, packaged, and stored.
[0024] A second aspect of the present invention provides a high-temperature proton exchange membrane fuel cell metal bipolar plate coating obtained by the above preparation method.
[0025] In this invention, the metal bipolar plate is made of 316L stainless steel or TA1 titanium alloy.
[0026] 1. Take a 10mm (length) × 10mm (width) × 0.1mm (thickness) piece of the coated metal bipolar plate and place it in a sulfuric acid solution with pH=3 and 5ppm fluoride ions. The test temperature is 120℃. Perform the following three corrosion tests.
[0027] 1) Potential dynamic corrosion test Apply -0.6~1.2V ( vs The potential of Ag / AgCl was obtained by fitting the self-corrosion current density using TAFEL (Tafel extrapolation method).
[0028] 2) Constant potential durability corrosion test Apply 0.84V ( vs The potential of Ag / AgCl was measured for more than 8 hours, and the corrosion current density was observed.
[0029] 3) Constant potential accelerated corrosion test Apply 1.6V ( vsThe potential of Ag / AgCl was measured for a duration of not less than 1 hour, and the corrosion current density was observed.
[0030] 2. Contact resistance test The contact resistance test should be conducted according to the procedure specified in GB / T 20042.6-2024, and the contact resistance value at 0.6 MPa should be recorded. The smaller the value, the better the conductivity.
[0031] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.002, 28, and 83 μA / cm, respectively. 2 The contact resistance is 2.06 mΩ·cm. 2 .
[0032] Example 2 The specific implementation method in this example is the same as in Example 1, except that the low-temperature Ar plasma activation treatment is 30 min.
[0033] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.003, 25, and 79 μA / cm, respectively. 2 The contact resistance is 2.27 mΩ·cm. 2 There is no significant difference from Example 1; the corrosion resistance and conductivity are similar, and the activation time (≥6 min) has little impact on the performance.
[0034] Example 3 The specific implementation method of this example is the same as that of Example 1, except that the working bias voltage in step S3 is -100V.
[0035] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.008, 35, and 88 μA / cm, respectively. 2 The contact resistance is 1.92 mΩ·cm. 2 The corrosion current density increased compared to Example 1, and the corrosion resistance was slightly worse. Therefore, the operating bias voltage has a slight impact on the corrosion resistance.
[0036] Example 4 The specific implementation method of this example is the same as that of Example 1, except that the arc source current of the graphite multi-arc target is 60A.
[0037] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.002, 30, and 81 μA / cm, respectively. 2 The contact resistance is 1.86 mΩ·cm. 2The test results were not significantly different from those of Example 1, with little difference in corrosion resistance and electrical conductivity.
[0038] Comparative Example 1 The specific implementation method of this example is the same as that of Example 1, except that step S3 is not included.
[0039] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.3, 93, and 223 μA / cm, respectively. 2 The contact resistance is 8.34 mΩ·cm. 2 Furthermore, the coating on the sample surface peels off after corrosion, and the corrosion resistance and conductivity decrease significantly. Removing the Ti transition layer will seriously affect the bonding between the coating and the metal substrate, thereby affecting its performance.
[0040] Comparative Example 2 The specific implementation method of this example is the same as that of Example 1, except that step S4 is not included.
[0041] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.008, 26, and 90 μA / cm, respectively. 2 The contact resistance is 10.28 mΩ·cm. 2 The conductivity of the product decreased significantly, so removing the carbon functional layer would seriously affect its conductivity.
[0042] Comparative Example 3 The specific implementation method in this example is the same as in Example 1, except that carbon deposition in step S4 is replaced with Pt deposition.
[0043] in: 1. High-purity platinum targets require a platinum purity of ≥99.99%; 2. The deposition equipment has two sputtering plane target positions, with a high-purity titanium target and a platinum target installed at each of the two sputtering plane target positions; 3. First, a titanium transition layer is prepared by magnetron sputtering, then a co-sputtering transition layer is prepared by dual-target magnetron sputtering, and finally a platinum film layer is prepared by magnetron sputtering. 4. Specific process parameters: 4.1 The titanium transition layer process remains unchanged; 4.2 Co-sputtering transition layer: Rotary frequency 40~60 Hz (planetary motion, spindle 3~6 rpm), argon gas is introduced, argon gas flow rate 50 sccm, working pressure 0.2 Pa, DC power supply 1 current 20 A, DC power supply 2 current 15 A, sputtering time 5 min, bias voltage -50V; 4.3 Surface Pt layer: Rotary rack frequency 100 Hz, argon gas introduced, argon gas flow rate 100 sccm, working pressure 0.8 Pa, DC power supply current 15 A, sputtering time 15 min, bias voltage -100 V.
[0044] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.0078, 51, and 230 μA / cm, respectively. 2 The contact resistance is 0.94 mΩ·cm. 2 The product's conductivity is improved, but its corrosion resistance is greatly reduced, and the test success rate is very low. This is related to the fact that Pt easily promotes the occurrence of electrolytic reactions, and the cost is high.
[0045] Comparative Example 4 The specific implementation method in this example is the same as in Example 1, except that the titanium transition layer deposition time is 60 minutes.
[0046] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.012, 32, and 95 μA / cm, respectively. 2 The contact resistance is 1.82 mΩ·cm. 2 Furthermore, after constant potential corrosion, the coating on the sample surface peeled off, and the corrosion resistance decreased significantly, indicating that the Ti transition layer should not be too thick.
[0047] Comparative Example 5 The specific implementation method in this example is the same as in Example 1, except that the carbon deposition working pressure is adjusted to 0.8 Pa.
[0048] The test results for potentiodynamic corrosion testing, constant potential durability corrosion testing, and constant potential accelerated corrosion testing in this case were 0.028, 43, and 113 μA / cm, respectively. 2 The contact resistance is 3.36 mΩ·cm. 2 The corrosion resistance and electrical conductivity decreased to varying degrees, therefore the working pressure and vacuum level had an impact on the carbon coating's performance. 2 (Affects electrical conductivity) / sp 3 (Affects corrosion resistance) Formation has an impact.
Claims
1. A method for preparing a coating for a metal bipolar plate of a high-temperature proton exchange membrane fuel cell, characterized in that, Includes the following steps: S1. Pre-treatment before coating: After inspecting the incoming metal bipolar plates, ultrasonically cleaning and drying them, they are transferred to the composite magnetron sputtering coating equipment to clean the target and cavity of the equipment and complete the workpiece mounting. S2, Vacuum Degassing and Plasma Activation: After the cavity is roughly pumped by a mechanical pump, switch to a molecular pump to evacuate and degas while maintaining the temperature. Then, high-purity argon gas is introduced, the ion source is turned on, and low-temperature Ar plasma activation treatment is carried out. S3. Titanium transition layer deposition: Adjust the argon flow rate to the titanium deposition working pressure, use two high-purity titanium planar magnetron targets to perform titanium transition layer deposition, and obtain a dense titanium transition layer with a thickness of 25~40nm. S4. Carbon functional layer deposition: Adjust the argon flow rate to the carbon deposition working pressure, turn on the graphite multi-arc target, and perform carbon functional layer deposition to obtain a carbon functional layer. S5. Post-processing: After coating is completed, the coating is cooled in a controlled manner, then inspected, packaged, and stored. The low-temperature Ar plasma activation treatment has an Ar flow rate of 57~63 sccm, a working pressure of 0.75~0.85 Pa, a treatment time of ≥6 min, and a pulse bias voltage of -240~-260 V; The deposition time for the titanium transition layer is 4-5 minutes. The working pressure for carbon deposition is 0.07~0.09 Pa.
2. The preparation method according to claim 1, characterized in that, The vacuum degree in step S2 is ≤8×10 - 4 Pa.
3. The preparation method according to claim 1, characterized in that, The temperature for the heat preservation and degassing treatment is 90~100℃, and the time is 40~50min.
4. The preparation method according to claim 1, characterized in that, The high-purity argon gas has a purity of ≥99.999% and a dew point of ≤-60℃.
5. The preparation method according to claim 1, characterized in that, The Ar flow rate in step S3 is 20~30 sccm.
6. The preparation method according to claim 1, characterized in that, The working pressure for titanium deposition is 0.1~0.15 Pa.
7. The preparation method according to claim 1, characterized in that, The high-purity titanium planar magnetron target has a single target power of 4~5kW, a target-to-substrate distance of 120~150mm, and a purity of ≥99.95%.
8. The preparation method according to claim 1, characterized in that, The operating bias voltage for the titanium transition layer deposition treatment is -50 to -100V.
9. The preparation method according to claim 1, characterized in that, The arc source current in the carbon functional layer deposition process is 50~60A, the peak bias voltage of the workpiece is -37~-43V, and the deposition time is 10~15min.
10. A high-temperature proton exchange membrane fuel cell metal bipolar plate coating prepared by the method of preparing the high-temperature proton exchange membrane fuel cell metal bipolar plate coating according to any one of claims 1 to 9.